Konseptualisasi Pengaduan Konstitusional (Constitutional Complaint) Sebagai Salah Satu Upaya Perlindungan Hak Konstitusional Warga Negara - Christo Sumurung Tua Sagala (USU LAW JOURNAL, 2019)
Abstract. Constitutional right is basic right of citizens which guaranteed the Constitution. Constitutional right must be protected and honoured by all of department state authority. Therefore there must be a legal remedy as a mechanism to achieve such protection so that the rights owners can defend their rights if happened violation. Constitutional Complaint is one of Law remedy. By Constitutional Complaint, the Constitutional protection right of citizens will more maximum, because citizens can propose supplication directly if they fell there is right which loss. Constitutional Court as Guardian and The Protector of the Constitution of The Republic Indonesia 1945, is the state institutions which deserve to be given the authority to finish the problem Constitutional Complaint. Many supplication which consist subtantion of Constitutional Complaint have been proposed to Constitutional Court is one of important reason of giving authority to Constitutional Court to finish the problem of Constitutional Complaint. Method of collecting data is done by literature review, observation, interview, and then the data is analized and make conclusion from all of data which has been got. The result from research that Constitutional Court of The Republic Indonesia hasn’t authority to finish the problem of Constitutional Complaint. Keywords: constitutional right, complaint